Parish Records of Orthodox Churches in Toplica from the End of the 19th and the Beginning of the 20th Century as a Historical Source - Stanojević, Saša D.; Marsenić, Miloš M. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
Parish records are an important historical source for demographers and historians. They contain various data of importance for researchers: records of births, marriages, and deaths, then dates, names, surnames, occupations, diseases, etc. The paper analyses the archival material through the preserved parish records of the temples of the Serbian Orthodox Church in the Toplica area. Individual birth, marriage, and death records, are part of the Collection of Registers of the Historical Archive of Toplica in Prokuplje. Based on various data they contain, this original documentary material is suitable for research not only in this area, but also for wider demographic conditions, since the newly liberated parts of Serbia had been deserted since 1878 and inhabited by people from various parts of the Serbian ethnic area.
Keywords: Toplica; 1878–1918; Parish records; Orthodox churches; Archives